Illocutionary Speech Act of Hate Speech in Mobile Legends Game - Gusti, Dharma; Syahid, Agus; Sudewi, Ni Ketut Putri Nila; Abdussamad, Zainuddin; Sutarman (LPPM Universitas Dhyana Pura, 2025)
Hate speech appears as a form of players' emotional response to the tense and competitive game situation. The purpose of this study is to identify the types of speech acts used in hate speech and analyze the form of hate speech in the Mobile Legends chat and comments. The method used was descriptive qualitative with a pragmatics approach regarding Searle illocutionary theory and used documentation techniques on conversation in chat games and player comments. The results showed that expressive speech acts are the most dominant 65form (53,33%), followed by directive (33.33%), assertive (6.67%), and commissive (6.67%). The forms of hate speech are carried out through calling someone or a group of people with animals, parts of the human body, blasphemy, and also Psychological Abuse. This speech not only reflects emotions, but is also used as a tool to verbally and psychologically attack opponents. The findings prove that in-game hate speech is a meaningful social action that can influence interactions between players. This study emphasizes the importance of understanding pragmatics in unpacking the meaning of hate speech as well as the urgency of creating a healthy play environment free from verbal violence.